Composites techniques optimization and finite element analysis of kenaf fiber reinforced epoxy nonwoven composite structures for renewable energy infrastructure - Owen M.M.; Wong L.S.; Achukwu E.O.; Romli A.Z.; Nazeri M.N.; Shuib S. (SAGE Publications Ltd, 2025)
In exploring the viability of kenaf fiber-reinforced epoxy nonwoven composites (KFRECs) for renewable energy infrastructure, the optimization of their manufacturing techniques for maximum performance remains a significant research gap. This study addresses this challenge by investigating the optimization of nonwoven composites? fabrication techniques to enhance their mechanical, thermal, and microstructural robustness. Thus, an innovative vacuum double-bagging technique was compared with single-bagging and hand lay-up methods aimed at evaluating their impact on tensile and flexural strength, hardness, impact, and thermal resistance. The obtained results indicate that the vacuum single-bagging method significantly improved tensile and impact strength by 16% and 38.5%, respectively, while the vacuum double-bagging offered the greatest improvements in flexural strength and hardness, with increases of 112.6% and 15.3%, respectively, compared to the hand lay-up technique. SEM analysis confirmed the vacuum processing techniques produced well-consolidated composite structures with uniform fiber distribution, complete wettability, a good fiber-matrix interface, and a reduced void content, leading to improved material properties. Finite Element Analysis (FEA) simulations revealed a variation in tensile stress of approximately 22.4% and a close agreement with a minimal variation of 2.1% in flexural stress, further validating these optimized techniques. The results also correlate with enhanced thermal behavior and rigidity at elevated temperatures, with the vacuum double-bagging technique exhibiting the highest thermal stability for the demanding conditions of the energy infrastructure sector. The study concludes that the choice of fabrication technique is pivotal for advancing the design, properties and performance of KFRECs, for sustainable energy structures. ? The Author(s) 2024.